Effect of Applying Progressive Muscle Relaxation Activities of Daily Living in Multiple Sclerosis Patients - Somayyeh Ghaffari; Fazlollah Ahmadi; Seyyed Masoud Nabavi; Robabeh Me'marian; Anoushirvan Kazem-Nejad (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Multiple Sclerosis (MS) is one of the most common chronic unpredictable demyelinization diseases of the Central Nervous System (CNS). The aim of this study is to assess the effect of applying the Progressive Muscle Relaxation on activities of daily living of Multiple Sclerosis patients. Materials & Methods: This is a interventional and experimental study. Sixty six Multiple Sclerosis patients were selected with non probability sampling according to specific criteria then assigned to experimental and control groups (33 patients in each group) with random allocation. Data collector tools included: demographic questionnaire, ADL-MS questionnaire and self report checklists. Progressive Muscle Relaxation (PMR) performed for 63 sessions by experimental group during two months but no intervention was done for control group. Data was analyzed by suing statistical analysis such as paired T-test, independent T-test, ANOVA and correlation coefficient determination.  Results: The findings showed that there is no significant difference between two groups in mean scores of ADL before the study (P>0/05) but there are significant differences, within one and two months after intervention (P<0/05). ANOVA test with repeated measurements showed that there is a significant difference in mean score of social dimension of ADL between two groups in 3 times (P<0/02), but no significant difference in mean scores of another dimensions of ADL (physical, sensory, intimacy) and whole ADL (P&ge0/095). Conclusion: The results of this study show that Progressive Muscle Relaxation (PMR) is practically feasible and may be associated with Activities of Daily Living (ADL) increase in Multiple Sclerosis (MS) patients. Therefore, applying such technique can promote Multiple Sclerosis patients Activities of Daily Living.